(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses the important role of intercultural communication competence in learning a foreign language. Developing this competence improves the language learning process as it helps learners better interpret cultural contexts, avoid misunderstandings, and gain a deeper understanding of the language’s nuances.